Analisis Efektivitas Pelaksanaan Anggaran Belanja BAPPEDA Toraja Utara - Tangdialla, Randi; Datu, Riva (UKI Toraja Press, 2021)
This study aims to analyze the effectiveness of achieving the implementation of the budget at BAPPEDA North Toraja. The data used in this study is the 2015-2019 budget realization report from BAPPEDA North Toraja. The data analysis technique used in this research is to use the effectiveness formula which is measured by comparing the realization of the budget with the target of the budget. Based on the results of the analysis, the effectiveness of the BAPPEDA North Toraja is good because it is still in the category of quite effective to effective. Although it shows fluctuating effectiveness results from 2015-2019.